2014
DOI: 10.1111/jmp.12140
|View full text |Cite
|
Sign up to set email alerts
|

Balantidium coli and other gastrointestinal parasites in captives non‐human primates of the Rio de Janeiro, Brazil

Abstract: These results demonstrated the need for implements of sanitation programs in the sites for captive primates nurturing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
3
19
1
Order By: Relevance
“…In non-human primates, several studies have reported a prevalence between 0.5% and 44.4% [ 69 72 ]. The genetic assemblage A was detected in primates kept in a zoo, which highlights that, considering the zoonotic potential of the assemblage detected, regular coproparasitological surveys are necessary to safeguard the captive animals, their caretakers and people visiting zoos [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In non-human primates, several studies have reported a prevalence between 0.5% and 44.4% [ 69 72 ]. The genetic assemblage A was detected in primates kept in a zoo, which highlights that, considering the zoonotic potential of the assemblage detected, regular coproparasitological surveys are necessary to safeguard the captive animals, their caretakers and people visiting zoos [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genotype AI was also detected in captive Alouatta clamitans in the south of the country, indicating that these animals might be susceptible to infection with G . duodenalis strains of human origin [ 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…and the ciliates Balantioides coli and Troglodytella abrassarti are also a common finding in the faeces of captive NHP ( Johnson-Delaney, 2009 ; Medkour et al, 2020 ; Helenbrook and Whipps, 2021 ). All the above-mentioned protist species have been documented in NHP collections of zoological gardens and sanctuaries in Asian ( Mul et al, 2007 ; Nath et al, 2012 ; Du et al, 2015 ; Adrus et al, 2019 Zhao et al, 2020 ), African ( Munene et al, 1998 ; Pomajbíková et al, 2010a , b ; Li et al, 2011 ; Mbaya and Udendeye, 2011 ; Ryan et al, 2012 ; Adetunji, 2014 ; Debenham et al, 2015 ; Kouassi et al, 2015 ), American ( Phillips et al, 2004 ; Wenz et al, 2010 ; Milozzi et al, 2012 ; da Silva Barbosa et al, 2015 ), and European ( Levecke et al, 2007 ; Berrilli et al, 2011 ; Köster et al, 2021a ) countries. These studies revealed marked differences in occurrence rates depending on host species, geographical location, and detection method used.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal parasites have been monitored in neotropical primates [ 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]; however, they are restricted to some countries such as Mexico [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] and Brazil [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Regarding the study of hemoparasites and arboviruses in neotropical primates, this one is restricted just to a few studies in Brazil [ 45 , 46 , 47 , 48 ], Venezuela [ 49 , 50 ] and French Guiana [ 49 ], and Ecuador has no data on them [ 51 ], even if most of those hemoparasites and arboviruses are present in Ecuador [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%